A 50‐nm‐Sized Micellar Assembly of Thermoresponsive Polymer‐Antisense Oligonucleotide Conjugates for Enhanced Gene Knockdown in Lung Cancer by Intratracheal Administration. Issue 2 (21st November 2019) - Kim, Beob Soo; Osawa, Shigehito; Naito, Mitsuru; Ogura, Satomi; Kamegawa, Rimpei; Ishida, Hiroki; Kim, Hyun Jin; Uchida, Satoshi; Miyata, Kanjiro
Abstract: For intratracheal delivery of antisense oligonucleotides (ASOs) to lung cancer, a nano‐sized micellar assembly is fabricated from an ASO conjugate with thermoresponsive poly(2‐ n ‐propyl‐2‐oxazoline) (POX). POX‐ASO conjugate is prepared via a copper‐free click conjugation between azide‐terminal POX and dibenzocyclooctyne‐terminal ASO. Through the thermoresponsive transition of the POX segment from hydrophilic to hydrophobic at temperatures above a critical solution temperature, a 50‐nm‐sized micellar assembly with a narrow size distribution is successfully fabricated when the hydrophobicity of POX segment is strengthened by increasing the molecular weight to 30 kDa. The micellar assembly, termed "ASOball", elicits more efficient cellular uptake of ASO and significantly higher gene knockdown, compared with non‐conjugated ASO, with negligible cytotoxicity in cultured human lung cancer cells. When the ASOballs are intratracheally administrated into an orthotopic lung cancer model mouse, they show enhanced retention in the tumor tissue 24 h post‐administration, compared with non‐conjugated ASO. Ultimately, the ASOballs significantly reduce the expression level of target long noncoding RNA (lncRNA) by ≈55% at a dose of 15 µg per mouse in a sequence‐specific manner 72 h post‐administration, whereas no significant knockdown effect is observed for non‐conjugated ASO. These results demonstrate the strong potential of ASOballs for intratracheal ASO delivery to lung cancers. Abstract : A 50‐nm‐sized micellar nanoparticle (ASOball) is fabricated from thermoresponsive polymer‐antisense oligonucleotide (ASO) conjugates for the ASO delivery to lung tumors by intratracheal administration. The utility of this strategy is demonstrated by results that show that the ASOballs show prolonged retention in the lung and in lung cancer cells, and the enhanced gene knockdown in the lung cancer after intratracheal administration.